2016
DOI: 10.1016/j.jns.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Canine olfactory ensheathing cells from the olfactory mucosa can be engineered to produce active chondroitinase ABC

Abstract: A multitude of factors must be overcome following spinal cord injury (SCI) in order to achieve clinical improvement in patients. It is thought that by combining promising therapies these diverse factors could be combatted with the aim of producing an overall improvement in function. Chondroitin sulphate proteoglycans (CSPGs) present in the glial scar that forms following SCI present a significant block to axon regeneration. Digestion of CSPGs by chondroitinase ABC (ChABC) leads to axon regeneration, neuronal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Compared with previous reports, the transfection levels we have obtained for cOMCs appear to be within ranges reported for viral methods: Carwardine et al 17 reported a maximum transduction efficiency of 34% at a multiplicity of infection (MOI) of 10, using chondroitinase ABC encoding lentiviral vectors and Ruitenberg et al 31 reported 100% transduction of rodent olfactory bulb-derived OECs with a reporter plasmid at an MOI of 50 and 100 using lentiviral and adenoviral vectors, respectively. Wu et al 32 transfected purified rodent olfactory bulb-derived OECs with a plasmid encoding NT-3 using a commercial lipofection agent, reporting a maximum transfection efficiency of 30% showing our techniques also compare favourably with other non-viral methods.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Compared with previous reports, the transfection levels we have obtained for cOMCs appear to be within ranges reported for viral methods: Carwardine et al 17 reported a maximum transduction efficiency of 34% at a multiplicity of infection (MOI) of 10, using chondroitinase ABC encoding lentiviral vectors and Ruitenberg et al 31 reported 100% transduction of rodent olfactory bulb-derived OECs with a reporter plasmid at an MOI of 50 and 100 using lentiviral and adenoviral vectors, respectively. Wu et al 32 transfected purified rodent olfactory bulb-derived OECs with a plasmid encoding NT-3 using a commercial lipofection agent, reporting a maximum transfection efficiency of 30% showing our techniques also compare favourably with other non-viral methods.…”
Section: Discussionsupporting
confidence: 76%
“…This means that the additional benefits provided by the MP platform, such as the use of bimodal nanoparticles for simultaneous gene delivery and imaging 27 could be safely exploited. Future work will deploy this therapy in vivo in clinical spinal injuries (including in canine trials), and explore the ability of this technical approach to deliver other genes involved in repair such as additional neurotherapeutic factors to promote growth, chondroitinase ABC to degrade the glial scar, 17,46 and VEGF to promote local angiogenesis. 47…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lentiviral transfer vector used to deliver the mammalian-compatible Proteus vulgaris ChABC gene [ 22 ] and the GFP gene to canine OECs was identical to the pRRL-CMV-ChABC-SFFV-GFP vector previously reported [ 37 ]. The control transfer vector pRRL-CMV-GFP expressed solely GFP.…”
Section: Methodsmentioning
confidence: 99%
“…Canine OECs can be safely collected from the nasal mucosa, cultured in vitro and autologously transplanted into spinal cord lesions [ 30 ]. We have previously demonstrated that these canine OECs can be genetically modified to produce the mammalian-modified form of ChABC in vitro [ 37 ]. We further show here that canine OECs can act as a vehicle for delivering active ChABC to the site of SCI in rats.…”
Section: Introductionmentioning
confidence: 99%